Molecular epidemiology of contagious bovine pleuropneumonia by detection, identification and differentiation of mycoplasma mycoides mycoides in Niger State, Nigeria (2015)
The study was aimed at epidemiologically detecting, identifying, and differentiating Mycoplasma mycoides subsp. mycoides strains according to their geographical origins in asymptomatic cattle populations of Niger State, North-central Nigeria between January and August 2013, using conventional and fingerprinting PCR assays without culturing or enriching of the field samples. Cross sectional molecular study of asymptomatic cattle sampled in the major abattoirs and livestock markets was carried out. Geographical lineage differentiation of the strains was performed on the basis of presence or absence of 8.84 kb genomic segment. With primers pair MM450/MM451, two 574 bp genomic fragments of DNA of Mycoplasma mycoides subsp. mycoides were detected. Using fingerprinting PCR; with insertion element IS1296/R(all) primers pair the detected two strains of Mycoplasma mycoides subsp. mycoides genomic DNA were specifically identified by generation of a fragment of 1.1 kb; with IS1296/R1 primers pair, identified Mycoplasma mycoides subsp. mycoides strains were differentiated to be of African cluster by generation of 1.4 kb. The PCR procedures were sensitive and produced rapid results that identified two strains of Mycoplasma mycoides subsp. mycoides of African/Australian origin. The presence of Mycoplasma mycoides subsp. mycoides African/Australian strains, which is useful for vaccine production, was therefore established in Niger State, Nigeria.